Myc is a prognostic biomarker and potential therapeutic target in osteosarcoma. (May 2020) - Feng, Wenlong; Dean, Dylan C.; Hornicek, Francis J.; Spentzos, Dimitrios; Hoffman, Robert M.; Shi, Huirong; Duan, Zhenfeng
Background: Over the past four decades, outcomes for osteosarcoma patients have plateaued as there have been few emerging therapies showing clinical results. Thus, the identification of novel biomarkers and therapeutic strategies are urgently needed to address these primary obstacles in patient care. Although the Myc-oncogene has known roles in oncogenesis and cancer cell growth, its expression and function in osteosarcoma are largely unknown. Methods: Expression of Myc was determined by Western blotting of osteosarcoma cell lines and patient tissues, and by immunohistochemistry of a unique osteosarcoma tissue microarray (TMA) constructed from 70 patient samples with extensive follow-up data. Myc specific siRNA and inhibitor 10058-F4 were applied to examine the effect of Myc inhibition on osteosarcoma cell proliferation. The clonogenicity and migration activity was determined by clonogenic and wound-healing assays. A mimic in vivo assay, three-dimensional (3D) cell culture model, was performed to further validate the effect of Myc inhibition on osteosarcoma cell tumorigenic markers. Results: Myc was significantly overexpressed in human osteosarcoma cell lines compared with normal human osteoblasts, and also highly expressed in fresh osteosarcoma tissues. Higher Myc expression correlated significantly with metastasis and poor prognosis. Through the addition of Myc specific siRNA and inhibitor, we significantly reduced Myc protein expression, resulting in decreased osteosarcoma cell proliferation. Inhibition of Myc also suppressed the migration, clonogenicity, and spheroid growth of osteosarcoma cells. Conclusion: Our results support Myc as an emerging prognostic biomarker and therapeutic target in osteosarcoma therapy.